2021
DOI: 10.3389/fcell.2021.638710
|View full text |Cite
|
Sign up to set email alerts
|

Biological Functions of Gasdermins in Cancer: From Molecular Mechanisms to Therapeutic Potential

Abstract: Pyroptosis is a type of lytic programmed cell death triggered by various inflammasomes that sense danger signals. Pyroptosis has recently attracted great attention owing to its contributory role in cancer. Pyroptosis plays an important role in cancer progression by inducing cancer cell death or eliciting anticancer immunity. The participation of gasdermins (GSDMs) in pyroptosis is a noteworthy recent discovery. GSDMs have emerged as a group of pore-forming proteins that serve important roles in innate immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 136 publications
0
21
1
Order By: Relevance
“…Mitochondrial dysfunction could trigger caspase-9 activation and subsequently cleaves and activates caspase-3. Active caspase-3 then cleaves GSDME to GSDME-NT, thus leading to pore-formation on the cell membrane, which is the hallmark for pyroptosis ( Wang et al, 2021b ). When GSDME is defective, cells are more prone to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction could trigger caspase-9 activation and subsequently cleaves and activates caspase-3. Active caspase-3 then cleaves GSDME to GSDME-NT, thus leading to pore-formation on the cell membrane, which is the hallmark for pyroptosis ( Wang et al, 2021b ). When GSDME is defective, cells are more prone to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis could promote anti-tumor inflammatory responses and tumor regression; however, on the contrary, other studies found that pyroptosis may also facilitate the supportive tumor microenvironment. ( Hergueta-Redondo et al, 2014 ; Gao et al, 2018 ; Wang et al, 2018 ; Tan et al, 2020 ; Wang et al, 2021a ; Loveless et al, 2021 ). Thus, the role of pyroptosis remains inconclusive and may differ in different tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, moderate pyroptosis is conducive to the timely removal of infected cells. Nevertheless, excessive activation of pyroptosis leads to a large number of cell deaths and inflammatory cascade reactions, seriously damaging tissues and organs, and even leading to organ failure, which is closely related to the pathogenesis of certain diseases (75)(76)(77)(78)(79). A large number of studies have shown that pyroptosis is widely involved in the occurrence and progression of infectious diseases (80), metabolic diseases (81), tumors (82), nervous system diseases (83) and cardiovascular diseases (84).…”
Section: Role Of Pyroptosis In Diseasesmentioning
confidence: 99%
“…Given the dual role of pyroptosis, its molecular components are, as one would expect, abnormally and differentially expressed across different cancers (Table 2 ). GSDMs, for instance, are deregulated in breast, gastric, cervical, and lung cancers, among others, and have been shown to control proliferation, metastasis, therapeutic resistance, and antitumor immunity while acting as either oncogenes or tumor suppressors [ 65 , 66 ]. In gastric cancer (GC), GSDMD expression was markedly decreased and resulted in enhanced tumor proliferation both in vitro and in vivo, possibly by accelerating S/G2 cell transition [ 57 ].…”
Section: Pyroptosis and Its Constituents In Cancermentioning
confidence: 99%